2014
DOI: 10.1007/s12010-014-1011-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Heat-Related ESTs in Moth Bean Through Suppression Subtraction Hybridization

Abstract: Moth bean (Vigna aconitifolia (Jacq.) Marechal), an important grain-legume crop grown in hot desert regions of Thar, under scorching sun rays, was investigated for heat tolerance at molecular level. In the present study, we constructed a forward suppression subtractive hybridization (SSH) cDNA library of heat tolerant genotype RMO-40 to identify genes expressing under delayed response to elevated temperature. Heat induction was carried out by exposing 14-day-old seedlings to elevated temperature of 42 °C for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…A similar pattern of gene expression was observed in tolerant and susceptible varieties of rice (Chen et al, 2014). The expression of HSPs is also observed in the moth bean heattolerant genotype RMO 40 under heat stress (42 °C for 30 min) (Gurjar et al, 2014) and these studies also validated the present observation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A similar pattern of gene expression was observed in tolerant and susceptible varieties of rice (Chen et al, 2014). The expression of HSPs is also observed in the moth bean heattolerant genotype RMO 40 under heat stress (42 °C for 30 min) (Gurjar et al, 2014) and these studies also validated the present observation.…”
Section: Discussionsupporting
confidence: 89%
“…However, the development of stress-tolerant varieties and their inclusion in crop improvement and breeding programs might be an optimistic approach. The genotypes RMO 40 and Jadia were considered as heattolerant in earlier studies (Gurjar et al, 2014;Sharma et al, 2014;Harsh et al, 2016), although RMO 40 was reported to be drought susceptible by Sachdeva et al (2016). Therefore, the genotypes with improved resistance and better performance under particular stress conditions need to be selected and studied for potentially important traits for use in breeding programs of moth bean.…”
Section: Introductionmentioning
confidence: 99%
“…C306. Secondary amplification of cDNA synthesis was visualized as a smear in the range of 100 bp to 1.5 kb on 1.2% agarose gel which indicated successful library preparation, and this result was in uniformity with Gurjar et al [ 11 ]. For identifying and enriching differentially expressed genes under HS in wheat cv.…”
Section: Discussionsupporting
confidence: 76%
“…For identifying and enriching differentially expressed genes under HS in wheat cv. C306, SSH has been an efficient approach in various crops [ 11 13 ]. We constructed two HS responsive forward SSH libraries (37°C HS and 42°C HS) at post anthesis stage in heat tolerant bread wheat cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation